A Model for Trans-Kingdom Pathogenicity in Fonsecaea Agents of Human Chromoblastomycosis - Fornari, Gheniffer; Gomes, Renata Rodrigues; Degenhardt-Goldbach, Juliana; Santos, Suelen Silvana dos; Almeida, Sandro Rogério de; Santos, Germana Davila dos; Muro, Marisol Dominguez; Bona, Cleusa; Scola, Rosana Herminia; Trindade, Edvaldo S.; Bini, Israel Henrique; Ferreira-Maba, Lisandra Santos; et al. (Frontiers in Microbiology, 2018)
The fungal genus Fonsecaea comprises etiological agents of human chromoblastomycosis, a chronic implantation skin disease. The current hypothesis is that patients acquire the infection through an injury from plant material. The present study aimed to evaluate a model of infection in plant and animal hosts to understand the parameters of trans-Kingdom pathogenicity. Clinical strains of causative agents of chromoblastomycosis were compared with a strain from a living plant. The clinical strains of F. monophora and F. pedrosoi were concentrated near the epidermis, whereas F. erecta colonized deeper plant tissues, resembling an endophytic behavior. In an invertebrate infection model with larvae of a beetle, Tenebrio molitor, F. erecta exhibited the lowest survival rates. However, F. pedrosoi produced dark, spherical to ovoidal cells that resembled muriform cells, the invasive form of human chromoblastomycosis confirming the role of muriform cells as a pathogenic adaptation in animal tissues. An immunologic assay in BALB/c mice demonstrated the high virulence of saprobic species in animal models was subsequently controlled via host higher immune response.